Transition Metal‐Free Radical α‐Oxy C−H Cyclobutylation via Photoinduced Hydrogen Atom Transfer. Issue 13 (24th May 2022) - Gao, Han; Guo, Lin; Shi, Chengcheng; Zhu, Yining; Yang, Chao; Xia, Wujiong
Abstract: A transition‐metal‐free photoinduced radical‐mediated α‐oxy C−H cyclobutylation reaction of bicyclo[1.1.0]butane (BCB) compounds was described. In this protocol, α‐oxy C( sp 3 )−H motifs including ethers and alcohols were activated via photocatalytic conditions, releasing the ring strain of BCBs and generating 1, 3‐disubstituted cyclobutanes in 40–80% yields. Control experiments and Stern‐Volmer quenching experiments indicated that the reaction proceeded through the generation of α‐oxy carbon‐centered radical intermediates by photoinduced hydrogen atom transfer (HAT) process. Abstract :